Enhanced Detection of Cognitive Radio Under Noisy Channels - Khanam, Sadiya; Kaur, Amandeep (International Journal of Computer Sciences and Engineering, 2025)
Cognitive radio have been considered as the able-bodied approach with the goal of enhancing spectral efficiency. The prime aim of cognitive radio is spectrum sensing. Spectrum sensing senses the presence of white spaces, but in fading environment unlicensed users are unable to discover the presence of licensed user in the band and this leads to interference. Therefore the aim of this paper is to increase SNR in two noisy environments, AWGN and Rayleigh Fading Environment using matched filter process and to increase lifetime of cognitive radio network using genetic algorithm.